An unusual case of coma related to glutamate receptor 3 (GluR3) auto-antibodies after a traumatic spinal cord injury: Clinical and pathological aspects. (June 2021) - Caputo, Fiorella; Barranco, Rosario; Ricci, Pietrantonio; Gratteri, Santo; Castelletti, Lara; Ravetti, Gian Luigi; Ventura, Francesco
We report the case of a 28-year-old patient with a history of post-traumatic epilepsy who, following a spinal cord injury and the onset of nosocomial infection, went into a deep coma. A brain MRI revealed non-specific findings, anti-Glutamate Receptor 3 (GluR3) auto-antibodies were detected in the liquor, and the patient's serum and immunomodulatory therapy proved ineffective. Autopsy and histological investigations led to the diagnosis of autoimmune encephalitis. This case highlights the diagnostic difficulties of a rare and still poorly researched disease and the possible role that traumatic and infectious episodes may play in the progression or acceleration of an immune response. As for patients with unexplained encephalitis, tests for autoantibodies against GluR3 in cerebrospinal fluid and serum should be considered. Forensic pathologists should be aware of encephalitis and epilepsies and that complete post-mortem investigations are required in such cases.